Stock Index Arbitrage in the Turkish Market - Slivka, Ronald T.; Biryol, Canel (Indian Journal of Finance, 2015)
For the first time in the Turkish stock market, the width of the zero arbitrage band for BIST 30 stock index arbitrage was measured and decomposed into distinct contributions arising from commissions, fees, bid/offer spreads, and stock loan costs. Intraday data was used to compute returns for forward and reverse BIST 30 arbitrage once per minute daily for 2014 and 2015 futures contracts. The absence of profitable trades and the unusual persistence of BIST 30 futures priced below the costless theoretical fair value were explained by their position within the zero arbitrage band. Measurement of arbitrage cost elements confirmed the need for regulatory policies to encourage development of domestic stock loan capabilities. The status of BIST 30 index arbitrage was compared with that occurring a decade ago, thereby contributing to the growing literature on the evolution of futures pricing efficiency in global markets after introduction of index futures.